Clinical Patterns Of Oro-facial Infections - Rahman, Z.A.A.; Hamimah, H.; Bunyarit, S.S. (2005)
The aim of this retrospective study was to study the clinical patterns of oro-facial infections presented and their management (or trends of management) at the Department of Oral and Maxillofacial Surgery, Dental Faculty, University of Malaya. These included the predisposing factors, presentations and management. This study reviewed the oro-facial infection cases over 15 years. The data was obtained from case note reviews of patients using specially designed proforma. A total number of 409 samples were included in this study. Majority of the patients were generally healthy with about 6.6% having diabetes mellitus. The common presentations were pain (47.4%), pus discharges (16.9%) and limitation of mouth opening (12.5%). The major site was in the submandibular region (18.9%) followed by cheek (13.2%). Most of the infections were from odontogenic source (63.2%). Other sources includes cysts (15.4%) and tumours (6.7%). Incision and drainage were the treatment of choice performed on 57.55% of patients. Monoantimicrobial therapy was the treatment instituted in 20.8% of cases.